2017
DOI: 10.1002/2017jd026604
|View full text |Cite
|
Sign up to set email alerts
|

Variations of global gravity waves derived from 14 years of SABER temperature observations

Abstract: The global gravity wave (GW) potential energy (PE) per unit mass is derived from SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) temperature profiles over the past 14 years (2002–2015). Since the SABER data cover longer than one solar cycle, multivariate linear regression is applied to calculate the trend (means linear trend from 2002 to 2015) of global GW PE and the responses of global GW PE to solar activity, to QBO (quasi‐biennial oscillation) and to ENSO (El Niño–Southern Oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
84
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 99 publications
(231 reference statements)
16
84
2
1
Order By: Relevance
“…The semiannual variations in zonal GW variances are consistent with other observations in the NH (Gavrilov et al, ; Placke, Stober, & Jacobi, ; Placke, Hoffmann, et al, ). In addition, the V‐shaped structure was also found in GW potential energy per unit mass derived from SABER from 70 to 100 km altitude at latitudes of 40°N and 50°N but was not found at 30°N (Liu, Yue, et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…The semiannual variations in zonal GW variances are consistent with other observations in the NH (Gavrilov et al, ; Placke, Stober, & Jacobi, ; Placke, Hoffmann, et al, ). In addition, the V‐shaped structure was also found in GW potential energy per unit mass derived from SABER from 70 to 100 km altitude at latitudes of 40°N and 50°N but was not found at 30°N (Liu, Yue, et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Without anything better, we use the observation at Collm as proxy as it is the result of 24 years of observation with overlapping altitudes which allows deduction of both 4-month summer and 6-month winter long-term GW variance trends. Figure 5 of Liu et al (2017) between 85 and 95 km of 40-50°N shows larger negative trends in May and June than the positive trends in July and August, giving rise to a net negative 4-month summer GW trend; similarly, it shows positive trends in November, December, and March with nearly zero trends in October, January, and February, giving rise to a net positive 6-month winter trend. Although the conclusion "The significant positive trend of GWs at around 50°N during July is consistent with that derived from medium-frequency radar observations in the height range of 80-88 km" {presumably referred to Hoffmann et al (2011), who reported the trend of GW variance (period 3-6 hr) between 1990 and 2010 at Juliusruh (55°N, 13°E) in July at this height range to be positive} does not agree with the observed negative July trend in Jacobi (2014), their signs for the 4-month summer and 6-month winter GW trends are consistent.…”
Section: Inspection Ofmentioning
confidence: 93%
“…The GW extraction method we use here is the same as that described in Appendix A of Liu et al (). The resolved GWs have λ z of 5–30 km.…”
Section: Methodsmentioning
confidence: 99%